2019
DOI: 10.3390/w11071515
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Local Scour Protection for Cylindrical Bridge Piers Using Anti-Scour Collars

Abstract: Local scour of bridge piers is one of the main threats responsible for bridge damage. Adopting scour countermeasures to protect bridge foundations from scour has become an important issue for the design and maintenance of bridges located in erodible sediment beds. This paper focuses on the protective effect of one active countermeasure named an “anti-scour collar” on local scour around the commonly used cylindrical bridge pier. A cylindrical pier model was set up in a current flume. River sand with a median pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Adopting scour countermeasures to protect bridge foundations from scour has become an important issue for the design and maintenance of bridges located in erodible sediment beds. Wang et al (2019n) studied the protective effect of one active countermeasure named an "anti-scour collar" on local scour around the cylindrical bridge pier by a live-bed scour experimental program. The effects of three design parameters including collar installation height, collar external diameter and collar protection range, on the scour depth and scour development were investigated parametrically.…”
Section: Bridge Scourmentioning
confidence: 99%
“…Adopting scour countermeasures to protect bridge foundations from scour has become an important issue for the design and maintenance of bridges located in erodible sediment beds. Wang et al (2019n) studied the protective effect of one active countermeasure named an "anti-scour collar" on local scour around the cylindrical bridge pier by a live-bed scour experimental program. The effects of three design parameters including collar installation height, collar external diameter and collar protection range, on the scour depth and scour development were investigated parametrically.…”
Section: Bridge Scourmentioning
confidence: 99%
“…Based on the above studies, it is inferred that installing the collar at lower levels and larger dimensions of the collar has the greatest effect on reducing the scour depth. Wang et al (2019) river sand with a median particle size of 0.324 mm was selected and used as the sediment. According to their experimental results, it can be concluded that: the application of an antiscour collar alleviates the local scour at the pier; and the protection decreases with an increase in the collar installation height, but increases with an increase in the collar external diameter and the protection range.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, active countermeasures are designed to decrease the intensity of the incoming flow by such as deflecting Fig. 1 Flow around a circular pier in a scour hole [5] the incoming flow, reducing the flow velocity to reduce the effects of downflow and horseshoe vortex, and thus protecting the bridge foundation from local scour [6,7].…”
Section: Introductionmentioning
confidence: 99%